Analyzing User Experience In The M-Tix Application Using The User Experience Questionnaire Method - Rayhan Ananda Hafiz Pradipta; Dimas Akbar Tama; Kinaya Khairunnisa Komariansyah; Hasna Nabiilah Widiani; Muhammad Ilham Nurfajri; Anka Luffi Ramdani; Irma Rasita Gloria Barus; Amata Fami (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The utilization of mobile applications in the service sector has experienced significant growth, fueled by increased access to the internet and the use of smartphones. The M-TIX app, which provides online movie ticket booking services, is one example of an app that has become an important part of movie fans' routines. Despite its popularity, users have reported various issues related to usability and overall user satisfaction. In this study, we focus on the user experience of the M-TIX app by using the User Experience Questionnaire (UEQ) to identify the strengths and weaknesses of the user experience aspects. Through a structured qualitative approach, the UEQ enables an in-depth evaluation of six key dimensions of user experience, namely Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The study involved respondents predominantly aged between 17 to 21 years old, with the largest group being 20 years old (15 respondents), and most of them (26 respondents) were students. The results of this study are expected to provide valuable recommendations for improving the design and functionality of the M-TIX application, as well as increasing the understanding of the relationship between users' characteristics and their perceptions of user experience in the context of online movie ticketing applications. This research aims to address the existing problems and enhance user satisfaction by providing actionable insights.